Dairy value chain in Uganda: Situation analysis and prospects - Agaba, Morris; Mukasa, Christopher (International Livestock Research Institute, 2024)
The dairy industry in Uganda has grown remarkably over the past two decades. Milk production has increased steadily from 0.4 to 3.1 billion litres per year and Uganda has changed from a net importer to a net exporter of milk and dairy products. However, domestic milk consumption the per capita consumption of 60 litres per year is still only 33% of that recommended by WHO. Progress in Uganda’s dairy sector development is a result of persistent and concerted action by public and private sectors. Notably; (1) the legislative, regulatory instruments and institutions, particularly the establishment of the pivotal DDA; (2) development actions by Send-a-Cow, Heifer International, and more recently SNV especially in the small-scale producer space; (3) research and development actions by CGIAR (ILRI and IFPRI), especially through the East African Dairy Development (EADD), and East African Dairy Genetics (EADG) projects, and (4) investments by the private sector in milk processing e.g. Jesa Farms Limited. Many other local and international actors have played a role, not least the farmers who have taken the risk to venture into dairy production amidst the many challenges. Further and accelerated growth is required to meet increasing domestic and regional demand for milk. Interventions to accelerate milk production should aim to increase farm productivity by strengthening producer organizations, improving farm business processes; and by the extending dairy investments beyond the southwestern and central Uganda milksheds. The sector has to over-come key challenges notably: 1. Inequities in the dairy value chain; low farm-gate price of milk amid increasing cost of production is cited as single most important indicator of inequity. 2. Gaps in the knowledge, skills and workmanship of the human resources along the value chain which in part contributes to inefficiency and low productivity reduces r competitiveness. 3. Adaptation to sustainable practices to mitigate climate change and constraints on natural esources. This study reviews the Uganda dairy industry addressing the following seven topics. 1. Structure, strengths, weakness opportunities and threat of the Uganda dairy value chain 2. Recent Dairy Development Initiatives and Investments. 3. Review of the role of Dairy cooperatives. 4. The Role of ICT (including Digital Solutions) in Uganda Dairy Production 5. Genetics, Genetics, Health & Feeding of Dairy Cattle 6. Research, Education and Extension Systems 7. Dairy Cattle Breeding Research and Delivery. 8. Uganda Dairy Value Chain in the context Uganda Vision 2040.